Application of generalized pressure perturbation principle to cubic equation of state formulation (2005)
Cubic equations of state are commonly used for predicting the properties of reservoir fluids. They are simple to use and require few parameters during computations. They have also been found to produce results that are comparable to the more rigorous multi-parameter equations. However, they are still regarded by many as mere comprehensive correlations of fluid properties because of a number of weaknesses and /imitations. This work addresses two weaknesses of cubic equations of state commonly highlighted in literature, viz: that they do not seem to have deep theoretical foundations and are not as accurate as non-cubic equations. A pressure perturbation technique based on a simple adaptation of the Weirtheim's first order thermodynamic perturbation theory has been developed and used to formulate a cubic equation of state. The practical equation formulated was applied to pure fluids and samples of Niger Delta Petroleum fluids. The results show more accurate predictions than the commonly used SRK and PR equations. This work suggests that cubic equations could have deeper theoretical.